Perceptions 2017: An international survey of library automation - Breeding, Marshall (Anuario ThinkEPI, 2018)
Results are presented of an online survey answered by 3,992 libraries in 87 countries between November 2017 and February 2018, based on their experiences with a total of 127 integrated library systems (ILS), both commercial and open source. The best products classified in their respective category analysed were Apollo (Biblionix), ByWater Solutions, Alma (Ex Libris), Polaris, Symphony (SirsiDynix), and Opals. The original English report was published on March 17th, 2018 on the author´s website: http://librarytechnology.org/perceptions/2017
Keywords: Survey; Study; Report; Evaluation; Classification; Ranking; Software; Library systems; ILS; Automation products; Business; Public libraries; University libraries; Academic libraries; School libraries; Habits; Trends.